Connectivism, Chaos and Chaoids: How Practitioners Might Find Inspiration from Chaos to Find New Spaces for Teaching and Learning - Shukie, Peter (PRISM: Casting New Light on Learning, Theory and Practice, 2019)
The rapid development of Web 2.0 technologies has created excitement and opportunity alongside fear and confusion. It seems no part of society, culture, economy and human life generally has been untouched as a new sense of chaos emerges. Across all sectors change has been experienced with a mixture of terror and exhilaration as disruption offers opportunity while often creating more oppressive structures than before. Alongside technological development has been the proliferation of a neoliberal takeover of the ways we live, work and educate; A social condition that Mark Fisher (2010) calls capitalist realism.  The impact of this growing sense of chaos on education seems significant if uncertain, generating transformative rhetoric if often ambiguous around what has been transformed. This paper looks at adult education as a space being fought over by increasingly corporate institutions and sees one thread of resistance, connectivism – a ‘new learning theory for the digital age’ - introducing chaos theory as a means of resistance. The paper goes on to argue that connectivism offers practical reflections without clear purpose. We need the philosophical purpose of Deleuze and Guattari’s approach to chaoids and chaos to go from identifying patterns to creating new forms of creating order. The paper includes a discussion on where we are now; what the significance of these two approaches to chaos are; provides exemplars of chaoids that respond to the challenge and provide alternative models of education.